Seroprevalence and distribution of leptospirosis serovars among wet market workers in northeastern, Malaysia: a cross sectional study - Ab Rahman, Mas Harithulfadhli Agus; Mohd Hairon, Suhaily; Hamat, Rukman Awang; Tengku Jamaluddin, Tengku Zetty Maztura; Shafei, Mohd Nazri; Idris, Norazlin; Osman, Malina; Sukeri, Surianti; A. Wahab, Zainudin; Wan Mohammad, Wan Mohd Zahiruddin; Idris, Zawaha; Daud, Aziah (BMC, 2018)
Background: Leptospirosis is a zoonotic disease associated with occupations which exposed workers to environments contaminated with urine of infected animals. The objective of this study was to determine the seroprevalence of leptospirosis among wet market workers in Kelantan. Methods: A cross sectional study was conducted in two main wet markets in Kelantan and 232 wet market workers were randomly selected. Blood samples were analysed for microscopic agglutination test (MAT) against 20 live leptospirosis reference serovars. MAT titres of 1:100 or more were considered as seropositive. Results: It was found that the overall seroprevalence for leptospirosis among the respondents was 33.6% (95% CI = 27.5, 39.7). The samples were tested positive against serovars Melaka (IMR LEP 1), Terengganu (IMR LEP 115), Sarawak (IMR LEP 175), Copenhageni (IMR LEP 803/11), Hardjobovis (IMR LEP 27), Australis, Autumnalis, Bataviae, Canicola, Grippotyphosa, Hardjoprajitno, Icterohaemorrhagiae, Javanica, Pyrogenes, Terrasovi, Djasiman, Patoc and Pomona. The predominant serovars was Autumnalis (18.2%). Conclusion: Wet markets workers were at risk for leptospirosis infection evidenced by high seroprevalence of leptospirosis in this study. Further research need to be conducted to determine factors that favours infection in this groups.